Revista Veja e a luta de classes dos anos 1980: FIESP e CNI contra CUT e o PT pelo olhar de Veja durante os anos 1985-1989 - Tostes, Suzane Conceição Pantolfi (2012)
The objective of this research is to investigate and analyze how Veja magazine made the cover over the role of class organizations (CUT, PT, FIESP e CNI) between the years 1985-1989. We assume that Veja magazine acts as a private apparatus of hegemony, since it proposes referrals, organize, create consensus and shares its world view with a certain fraction of the bourgeois class, in this period studied we concluded that Veja get closer of the fractions of the bourgeois class industrial business of the Brazil. The time frame of the research included the years 1985-1989, it was a remarkable period in Brazilian history, due to "end the military dictatorship" (but not the end of the rubble of authoritarian military dictatorship, once that, Constitution remained in force for the period of dictatorship until August 1988, the repression to the social movements and forms of mobilization and organization of the working class, the illegality of the strike, the permanence of the Ministry of Armed Forces and National Security all coordinated by the military), the promulgation of the New Constitution and with it the legality of the strike for some categories and the intensification of class struggle. Due to these factors the dissertation sought to discuss, analyze, investigate from the materials of the Veja magazine how it made the cover of the economic plans implemented during the years 1985 -1989 and the consequences for the working class. So as well as investigate the coverage that the magazine Veja made about the acting of the class organizations (CUT, PT, FIESP e CNI) in the period 1985-1989 and the clashes between these organizations